The Effectiveness of Yoga on Mental Health in The Elderly: A Literature Review - Kiki Rizki Dasaryandi; Novi Yulianti (International Journal of Medicine and Health, 2023)
Background: Mental disorders in the elderly are health problems that cause changes in older people's emotions, thoughts, and behaviors. This condition can cause the elderly difficulty functioning correctly in family, work, and social activities. To overcome the various problems that arise in the elderly, several modalities can be given, one of which is yoga. Objective: To find out the effect of yoga on mental health in the elderly by reviewing published research results. Research method: This research is a Literature review with the help of the PRISMA application in screening articles. In searching for articles using Publish or Perish, PubMed, and google scholar for the last seven years. Results: Yoga is an effective intervention given to the elderly, significantly reducing mental health disorders as support for the well-being of the elderly. Conclusion: Based on the results of the Literature Review study of 10 selected journals, it was found that the provision of yoga interventions effectively improved mental health in the elderly.